Non-Invasive Zinc Protoporphyrin Screening Offers Opportunities for Secondary Prevention of Iron Deficiency in Blood Donors - Schliemann, Anne; Homann, Christian; Hennig, Georg; Lang, Alexander; Holdt, Lesca Miriam; Vogeser, Michael; Sroka, Ronald; Stepp, Herbert; Weinauer, Franz; Quenzel, Ernst-Markus (Transfusion Medicine and Hemotherapy, 2023)
Background: Frequent blood donors are at high risk of developing iron deficiency. Currently, there is no potent screening during blood donation to detect iron deficient erythropoiesis (IDE) before anemia develops and deferral from donation is inevitable. Study Design and Methods: In addition to capillary and venous hemoglobin, the iron status of 99 frequent blood donors was assessed by various venous blood parameters and zinc protoporphyrin IX (ZnPP). ZnPP was determined by high-performance liquid chromatography (HPLC) and a new prototype fiber-optic device was employed for non-invasive measurements of ZnPP through the blood collection tubing (NI-tubing) and on lip tissue (NI-lip). We aimed to evaluate the feasibility and diagnostic value of the NI-tubing measurement for early detection of severe iron deficiency in blood donors. Results: NI-tubing and HPLC reference measurements of ZnPP showed narrow limits of agreement of 12.2 μmol ZnPP/mol heme and very high correlation (Spearman’s Rho = 0.938). Using a cutoff of 65 μmol ZnPP/mol heme, NI-tubing measurements (n = 93) identified 100% of donors with iron deficiency anemia (IDA) and an additional 38% of donors with IDE. Accordingly, NI-tubing measurements would allow detection and selective protection of particularly vulnerable donors. Conclusion: NI-tubing measurements are an accurate and simple method to implement ZnPP determination into the routine blood donation process. ZnPP was able to identify the majority of subjects with IDE and IDA and might therefore be a valuable tool to provide qualified information to donors about dietary measures and adjustments of the donation interval and thereby help to prevent IDA and hemoglobin deferral in the future.